The Analysis of The Effect of Tax Avoidance and Bankruptcy Risk on Cost of Debt in The Manufacturing Company Mining Subsector Listed in IDX 2015-2019 - Nurfathin, Dewi Indah (Jurnal KIAFE, 2021)
The purpose of this research is to determine the effects of tax avoidance and bankruptcy risk on cost of debt on mining companies listed in Indonesia Stock Exchange.This research is conducted as quantitative analysis. This research used 5 years of annual reports of mining company listed in Indonesia Stock Exchange and total of 151 samples from 30 companies ad was taken through the purposive sampling method. Findings reveal that tax avoidance has a non-significant negative effect on cost of debt means that if there is an income tax, using debt will improve the value of the company because interest on debt is a tax-deductible expense and bankruptcy risk has a significant negative effect on cost of debt means Bankruptcy can be defined as a circumstance or situation in which a company fails or is no longer able to meet its responsibilities to debtors as a result of a shortfall and inadequate cash to maintain or continue its operation, preventing the company from achieving its economic goals, namely profit.